If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 26 + -3x + -10 = 6 Reorder the terms: 26 + -10 + -3x = 6 Combine like terms: 26 + -10 = 16 16 + -3x = 6 Solving 16 + -3x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + -3x = 6 + -16 Combine like terms: 16 + -16 = 0 0 + -3x = 6 + -16 -3x = 6 + -16 Combine like terms: 6 + -16 = -10 -3x = -10 Divide each side by '-3'. x = 3.333333333 Simplifying x = 3.333333333
| 5(3x+20)=14(2x-3) | | 3q+7=6q-1 | | b^2=-4b-3 | | 5=n-6n | | =2.5 | | 8p+13=61 | | 2x^2+24x=176 | | 3x+9=8(x-16) | | 2(5+b)=3(b-2) | | (y-0)=-3(x-3) | | 8x=5x+7whatisx | | 0=8x^3-11x^2+14x-9 | | 8x+20=2x-10 | | 100-7r=45 | | 4+2(4x-6)=5-5(2x+1) | | 8x^4y^2+40x^2y^2-72x^2y= | | 3x=8x-119 | | 100-7t=44 | | 0.50+(12-x)=0.10(-57) | | x^3-12x^2-151x+1122=0 | | 22-7k=-2(6k-6) | | 4m^2-36m+81= | | -6=7x+-2 | | 6(3m+5)=-28 | | 33=8+5t | | -92=7(a-8)+6 | | 8y-10=0 | | 2.7xa=8.37 | | -3(x)=-3x*3+7 | | 2x-7=x+9 | | Ln(7-3x)=-4 | | (5m)+(2m)-5= |